ChemInform Abstract: Iodine‐Mediated Synthesis of Heterocycles via Electrophilic Cyclization of Alkynes. Issue 40 (September 2016) - Aggarwal, Trapti; Kumar, Sonu; Verma, Akhilesh K.
Abstract: Review: [78 refs.